2017
DOI: 10.14202/vetworld.2017.136-139
|View full text |Cite
|
Sign up to set email alerts
|

Associations between single nucleotide polymorphisms in multiple candidate genes and body weight in rabbits

Abstract: Aim:In this study, we examined parts of six growth genes (growth hormone [GH], melanocortin 4 receptor [MC4R], growth hormone receptor [GHR], phosphorglycerate mutase [PGAM], myostatin [MSTN], and fibroblast growth factor [FGF]) as specific primers for two rabbit lines (V-line, Alexandria) using nucleotide sequence analysis, to investigate association between detecting single nucleotide polymorphism (SNP) of these genes and body weight (BW) at market.Materials and Methods:Each line kits were grouped into high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
3
5
0
Order By: Relevance
“…In addition, the results of the nucleotide sequence analysis of the whole amplified fragments and the analysis of the means and standard errors of individual body weight at 63 days indicated a significant association between the MC4R SNPs and high body weight of rabbits at market (63 days of age). This finding is in agreement with El‐Sabrout and Aggag (). The rabbit MC4R gene is produced in the hypothalamus (melanocortin 4 receptor), in which plays an area responsible for controlling feed intake behaviour (appetite), which in turn effect on body weight.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, the results of the nucleotide sequence analysis of the whole amplified fragments and the analysis of the means and standard errors of individual body weight at 63 days indicated a significant association between the MC4R SNPs and high body weight of rabbits at market (63 days of age). This finding is in agreement with El‐Sabrout and Aggag (). The rabbit MC4R gene is produced in the hypothalamus (melanocortin 4 receptor), in which plays an area responsible for controlling feed intake behaviour (appetite), which in turn effect on body weight.…”
Section: Discussionsupporting
confidence: 93%
“…It can stimulate the feed intake, metabolism and growth of egg, which in turn affect the egg weight. This finding is in agreement with ElSabrout and Aggag [17] , who found that MC4R plays an area responsible for controlling feed intake behavior, which in turn affect the body weight.…”
Section: Discussionsupporting
confidence: 92%
“…From a research point of view, one of the obvious candidate genes is the growth hormone gene (GH ), which has a critical role in animals' growth and tissue development (Amalianingsih and Brahmantiiyo, 2014;Abdel-Kafy et al, 2015;Zaghloul et al, 2019). Moreover, single nucleotide polymorphisms (SNPs) constitute a powerful method for detecting nucleotide sequence mutations in the amplified DNA (El-Sabrout and Aggag, 2017;El-Sabrout et al, 2019). Identification of SNPs in the rabbit has recently been started from re-sequencing of gene regions selected for different purposes (Fontanesi et al, 2012).…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%
“…Regardless of the large amount of data, mutations were not detected in the sequenced regions encompassing exons 2, 3 and 4, introns 1 and 3, and parts of introns 2 and 4. Accordingly, it was suggested that there is a lack in information of polymorphisms of GH gene, considering that this rabbit gene is located on chromosome 19 (Abdel-Kafy et al, 2016;El-Sabrout and Aggag, 2017). Since the GH gene plays an important role in rabbit growth efficiency, we consider the detection of sequence variations within this gene to be critical for rabbit selection programmes and navigation of the breeding process in this species.…”
Section: W O R L D R a B B I T S C I E N C Ementioning
confidence: 99%